Do Thyroid Disrupting Chemicals Influence Foetal Development during Pregnancy?. (11th September 2011) - Hartoft-Nielsen, Marie-Louise; Boas, Malene; Bliddal, Sofie; Rasmussen, Åase Krogh; Main, Katharina; Feldt-Rasmussen, Ulla
Abstract : Maternal euthyroidism during pregnancy is crucial for normal development and, in particular, neurodevelopment of the foetus. Up to 3.5 percent of pregnant women suffer from hypothyroidism. Industrial use of various chemicals—endocrine disrupting chemicals (EDCs)—has been shown to cause almost constant exposure of humans with possible harmful influence on health and hormone regulation. EDCs may affect thyroid hormone homeostasis by different mechanisms, and though the effect of each chemical seems scarce, the added effects may cause inappropriate consequences on, for example, foetal neurodevelopment. This paper focuses on thyroid hormone influence on foetal development in relation to the chemicals suspected of thyroid disrupting properties with possible interactions with maternal thyroid homeostasis. Knowledge of the effects is expected to impact the general debate on the use of these chemicals. However, more studies are needed to elucidate the issue, since human studies are scarce.